Living standards in Mexico during economic transition: Should we rely on a poverty line? - Rubalcava, Luis (Estudios Económicos de El Colegio de México, 2002)
Using household survey data from Mexico, this paper analyses the change in the standards of living during the period 1984 - 1994. We apply stochastic dominance to analyze changes in the welfare distribution. This study includes measures of sampling variation in the analysis and tests the significance of changes in household expenditures per capita using non-parametric statistical inference. Results show that Mexican families increased (on average) their purchasing power during this period, and that households with higher educational attainment of the head are relatively more sensitive to the business cycle.